A ação coletiva como forma de agregação no sistema agroindustrial da aquicultura de Maripá PR - Pasini, Andreia Helena (2013)
This dissertation has as its theme the collective action and the difficulties encountered by family farmers. As central question, we sought to answer what characteristics of cooperation to make a strategy that sustain us in the long term. As the object of study, it was investigated whether the agribusiness system (SAG) of pisciculture specifically the Association of Farmers Maripa and region (Aquimap). In This way, the objective of this study was to analyze the effect from an initiative of horizontal cooperation established by fish culturists family of the city of Maripa - PR, which factors have promoted and strengthened the Aquimap over time. The study was based on literature of collective actions, through the approaches with different approaches, seeking from these literatures the significant variables for the success or failure of a collective action. The empirical data were collected through interviews, questionnaires and records, performed with the associated with the entity, former president and the technician of Emater. For the analysis of the data, we used the descriptive analysis. The results showed that the majority of the variables analyzed as positive for collective action in study. However with regard to homogeneity and strong ties, it was observed as negative for the study, in spite of presenting as negative, the case empirical obtains success. Still meets highlight that the collective action obtains success over time, and the small family producers has remained with the production of fish. This study presents significant contribution to the studies of collective action, identifying the variables that can be considered as inductors of the success or failure of an action.